Gendered discourses and pejorative language use: An analysis of YouTube comments on We should all be feminists. (February 2023) - Diabah, Grace
Highlights: Discourses reflect ideologies. Ideologies often become akin to conflicts and social antagonism. Social media anonymity encourages pejorative language use. Gendered pejoratives reify the dichotomous relationship between men and women, not bridge it. Gendered pejoratives devalue the relevance of the socio-cultural issues under discussion. Abstract: Guided by Discourse and Ideology theory, this paper focuses on how authors of the YouTube comments on Chimamanda Adichie's talk ' We should all be feminists' use pejoratives or insults to reinforce or challenge certain gender ideologies and practices. Since feminism is already a thorny issue, Chimamanda's call for all to be feminists is seen as controversial and, thus, a recipe for inflammatory language use. Under the protection of social media anonymity, some participants therefore attack her, gender groups (or characteristics) or individuals who oppose their views. Emerging themes include perceiving feminism as toxic and women's success as a potential threat to male ego, among others. The paper concludes that reducing the discussion of such important social issues to insults does not only reify the dichotomy between men and women, which feminism seeks to bridge, but it also waters down the value and relevance of the socio-cultural issues being discussed.